Book Review: DOKTRIN KRISTEN: Perspektif Pentakosta, French L. Arrington - ELIA TAMBUNAN (BONAFIDE: Jurnal Teologi dan Pendidikan Kristen, 2026)
The book Christian Doctrine: A Pentecostal Perspective by French L. Arrington is a systematic theology rooted in the Pentecostal experience of faith. This book is an example that doctrine is not only an intellectual construction academically, but also a reflection on the work of the Holy Spirit in the contextual life of the church and believers based on the theological perspective of the Church of God (CoG) Denomination of one of the Pentecostal groups at the international level. Arrington outlines 10 central themes such as the Bible, God, creation, man, Christ, Sin, salvation, the Holy Spirit, the church, and the end times. This book is also seen as an inspiration for academic and theological enthusiasm for other academics to realize the independence of each church denomination to do theology in their respective contexts in the contemporary era.